Experimental Studies of Single-Layer Reticulated Domes with Isolated Supports - Guibo Nie; Kun Liu (Shock and Vibration)
To study the seismic behavior of a single-layer reticulated dome subjected to severe earthquakes, a series of shaking table tests were conducted for this paper. Seismic responses including the acceleration, displacement, and strains gathered at the members and nodes were discussed. The dynamic characteristics, including structure frequencies and damping ratio, were obtained through the results under the input excitation of white noise and the fast sine sweeping with different amplitudes. Various isolation devices usually installed in the upper portion of the structures have been widely used to reduce the dynamic responses for more than three decades. However, these isolation devices deal mostly with either horizontal isolation or vertical isolation, which is not applicable for synchronous isolation in both horizontal and vertical isolation. Therefore, an innovative isolated support for three-dimensional isolation was invented. In order to understand the earthquake-isolation effects of a single-layer reticulated dome with the isolated support, a series of shaking table tests were conducted. The dynamic behavior of the structure was then investigated and discussed using the acceleration and displacement responses of the tested structures with or without the isolated supports. The experimental results show that the isolated support invented in this study had a remarkable earthquake-isolation action in both horizontal and vertical isolation.